Spontaneous ovarian hyperstimulation syndrome and pituitary macroadenoma associated with primary hypothyroidism - Hossan, Md Shamim; Jahan, Sharmin; Sultana, Nusrat; Banu, Hurjahan; Hasanat, Muhammad Abul; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Ovarian hyperstimulation syndrome is associated with ovulation induction usually with gonadotropins and is rarely seen in pregnant women. Very few cases of spontaneous ovarian hyperstimulation syndrome have been reported in a woman who is neither pregnant nor undergoing ovulation induction therapy. Here we report an unsual case of a young adolescence girl with spontaneous ovarian hyperstimulation syndrome and pituitary macroadenoma. Her condition was triggered by unrecognized primary hypothyroidism, which regressed after treatment with levothyroxine and dopamine receptor agonist. This case highlights the need for clinicians and radiologists to familiarize themselves with the clinical and imaging features detected in this rare medical condition. Such improved knowledge will help to avoid delays in diagnosis, progression to life threatening complications, and unnecessary surgery. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 27-30